2017
DOI: 10.1080/17470218.2016.1275713
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Word Frequency on Peripheral Processes during Handwriting: A Matter of Age

Abstract: Although several studies have found that the sublexical route of spelling has an effect on handwriting movements, the ability of lexical variables to modulate peripheral processes during writing is less clear. This study addresses the hypothesis that word frequency affects writing durations only during writing acquisition, and that at some point of development, the handwriting system becomes a relatively autonomous system unaffected by lexical variables. Spanish children attending Grades 2, 4, and 6 performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 30 publications
10
38
0
Order By: Relevance
“…As in previous embodiment research on written production (García & Ibáñez, ; García‐Marco et al, ), the main measures of interest were FLL, calculated as the time between stimulus onset and the first contact of the pen with the tablet; and WWL, defined as the time between the first contact of the pen with the tablet and the last pen lift for a given stimulus. In line with reported protocols (Afonso et al, ; García & Ibáñez, ; García‐Marco et al, ; Roux, McKeeff, Grosjacques, Afonso, & Kandel, ), FLL yielded a measure of motor programming , whereas WWL reflected mechanisms operative in the execution of the writing routine.…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…As in previous embodiment research on written production (García & Ibáñez, ; García‐Marco et al, ), the main measures of interest were FLL, calculated as the time between stimulus onset and the first contact of the pen with the tablet; and WWL, defined as the time between the first contact of the pen with the tablet and the last pen lift for a given stimulus. In line with reported protocols (Afonso et al, ; García & Ibáñez, ; García‐Marco et al, ; Roux, McKeeff, Grosjacques, Afonso, & Kandel, ), FLL yielded a measure of motor programming , whereas WWL reflected mechanisms operative in the execution of the writing routine.…”
Section: Methodssupporting
confidence: 74%
“…We conducted two word‐copying experiments, one involving shallow processing and the other one requiring explicit semantic access. Guided by the HANDLE model, and considering that handwriting involves long response latencies (Afonso, Suárez‐Coalla, González‐Martín, & Cuetos, ; Damian & Stadthagen‐Gonzalez, ; Delattre et al, ) which surpass those proper to typing (García & Ibáñez, ) and fall within the timespan yielding facilitation effects on motor execution measures (e.g., Lugli et al, ), we hypothesized that production of MaVs would selectively reduce WWL—namely, the variable capturing motor execution duration.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with findings from McBride-Chang et al (2011), Lam and McBride (2018) surveyed 141 kindergartners in Hong Kong schools to explore the important role of handwriting skills in how children learn to spell Chinese words, and found that handwriting altogether significantly explained 10% of the variance in spelling accuracy, even after statistically controlling for the effects of age, non-verbal IQ, vocabulary knowledge, morphological awareness, orthographic awareness, and phonological awareness. Similar results were also seen in studies by Bosga-Stork et al (2016) and Afonso et al (2018), however, they further found that the effect only lasted until the third grade and disappeared in upper grades. Thus, they believed handwriting to be independent of spelling by the third grade.…”
Section: The Role Of Handwriting Fluency In Spelling Accuracysupporting
confidence: 88%
“…Due to the high demands of both handwriting and spelling processes during early writing acquisition, it is reasonably to think that age may play an important role in the level of parallel processing and the time-course of anticipation during writing. This issue has been mostly analyzed in studies investigating the written production of isolated words (Bonin and Fayol, 2002;Delattre et al, 2006;Lambert et al, 2011;Sausset et al, 2012;Afonso et al, 2018;Suárez-Coalla et al, 2018). Evidence obtained has shown that the impact of some linguistic factors on handwriting dynamics is different for different age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Kandel and Perret (2015a) found that phonology-to-orthography consistency affected the writing durations produced by French children between 8 and 10 years of age, but that the effect was larger for the younger children. Regarding word frequency, it has been found that this variable affects written latencies in both children and adults (Delattre et al, 2006;Lambert et al, 2011;Afonso et al, 2018), but its influence on writing durations seems to depend on the age of the writer (Søvik et al, 1994;Kandel and Perret, 2015b;Afonso et al, 2018;Suárez-Coalla et al, 2018). Afonso et al (2018) reported that the effect of lexical frequency in Spanish children strongly affected the writing durations of 8year-olds, but this effect decreased to disappear by 11 years of age.…”
Section: Introductionmentioning
confidence: 99%